Witness Sets, Polarity Reversal and the Processing of Quantified Sentences - Bott, Oliver; Klein, Udo; Schlotterbeck, Fabian (Proceedings of the Amsterdam Colloquium, 2013)
Experimental results show that the monotonicity of a quantifier (Q) affects how it is processed [4, 7, 6]. Qs are upward entailing (UE) if they permit inferences to supersets, i.e. from Q A B follows Q A B for any B B (e.g. every, at least ve). If from Q A B it follows that Q A B for any B B, the quanti er Q is downward entailing (DE) (e.g. no, at most ve). As compared to UE Qs, DE Qs are more difficult to verify [4, 7] and draw inferences from [6]. Recent attempts at deriving predictions about the processing of Q s are built on the notion of semantic automata [12], and have been presented e.g. in [11] and [10]. E.g., [11] improve on results by [8] by showing not only that the computational distinction between Q s recognized by nite-automata and push-down automata is psychologically relevant, but also that there are differences in the time required for verifying statements involving Q s even among the class of quanti ers recognized by nite state automata. However, since these approaches employ essentially the same kind of semantic automata for both DE and UE Qs, they cannot explain why DE Qs are more difficult to process than UE Qs. To explain this, we formulate a quantification theory which predicts that the (expansion) operation employed in processing DE Qs is more difficult than that for processing UE Qs, because it involves (i) inferences from negative information and (ii) polarity reversal. The predictions of our account were tested in two experiments investigating the online comprehension and verification of simply (Exp. 1) and doubly quantified sentences (Exp. 2) with UE vs DE Q s.